Disorder effect on the density of states in Landau quantized graphene: Graphene and graphite multilayers - Dóra, Balázs (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
We have studied the effect of gaussian potential (on-site) and unidirectional bond disorder on the density of states (DOS) of Landau quantized graphene. The broadening of the Landau levels weakly depends on energy and the symmetry of the disorder except at the Dirac point. There, bond disorder enhances significantlythe peak in the DOS. For stronger disorder, Landau quantization becomes irrelevant, the discrete structures from Landau levels disappear, and we recover the zero field DOS.